2019
DOI: 10.1108/lhs-11-2017-0066
|View full text |Cite
|
Sign up to set email alerts
|

Successful implementation of self-managing teams

Abstract: Purpose Following health-care organisations, many mental health-care organisations nowadays consider starting to work with self-managing teams as their organisation structure. Although the concept could be effective, the way of implementing self-managing teams in an organisation is crucial to achieve sustainable results. Therefore, this paper aims to examine how working with self-managing teams can be implemented successfully in the mental health-care sector where various factors for the successful implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Unfortunately, the authors did not report effect sizes or standard deviations, which inhibited conclusions regarding practical significance. Generally, good relationships were found relevant for SMT success (Sarker et al, 2011;Weerheim et al, 2019). One quasi-experimental study showed 3 months after an intervention to reinstall SMTs higher quality of team member exchange and cohesiveness in the SMTs than in the traditional teams (Seers et al, 1995).…”
Section: Relating and Networkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the authors did not report effect sizes or standard deviations, which inhibited conclusions regarding practical significance. Generally, good relationships were found relevant for SMT success (Sarker et al, 2011;Weerheim et al, 2019). One quasi-experimental study showed 3 months after an intervention to reinstall SMTs higher quality of team member exchange and cohesiveness in the SMTs than in the traditional teams (Seers et al, 1995).…”
Section: Relating and Networkingmentioning
confidence: 99%
“…This subcompetency includes putting effort and desire into one’s actions and showing determination to perform and reach goals. Research has identified as relevant making extra efforts to show commitment to the team and its goals, being proactive, and engaging proactively in problem-solving activities (Ainsworth, 2016; Druskat & Kayes, 2000; Hawkins, 2013; Moe et al, 2009; Weerheim et al, 2019). Specifically, personal and task commitment and perseverance were positively related to team performance and agile team maturity (Fontana et al, 2014; Gray, 2012).…”
Section: Individual Competencies For Smt Performancementioning
confidence: 99%
“…Health care organizations have been experimenting with different forms of autonomy in a range of practices from personal empowerment to self-managing teams, with ambiguous results. For example, in some health care organizations, nurses working in self-managing teams indeed reported more motivation and happiness (Weerheim, Van Rossum & Ten Have, 2019). However, in other health care organizations, nurses working in self-managing teams reported to be more demotivated and unhappy (Skipr, 2016).…”
Section: Meaningful Work Professional Autonomymentioning
confidence: 99%
“…If work provides opportunities for the development of job-specific skills as well as general problem-solving skills, social skills, and decision-making skills, it contributes to people flourishing even outside of work (Veltman, 2016, p. 5). Weerheim, Van Rossum, and Ten Have (2019), in their study on implementation of self-managing nursing teams, found that in self-managing nursing teams, nurses have several learning experiences in solving problems, decision-making, and communication. As a result, perceived group autonomy may be positively related to "expressing full potential.…”
Section: Expressing Full Potentialmentioning
confidence: 99%
“…Initiating self-organizing teamwork practices has also shown some promising results elsewhere: A study by Maurits, et al [32] showed that working in home care in a more self-organizing way was associated with higher job satisfaction. Moreover, in community mental health care, staff members were very satisfied with the increased independence and being able to influence their work more when self-organizing teamwork practices were initiated [33]. Increasing autonomy of teams has also shown to be associated with job satisfaction in other work sectors [34].…”
Section: Introductionmentioning
confidence: 99%